Pertumbuhan Kompensasi dan Efisiensi Produksi Ayam Broiler yang Mendapat Pembatasan Waktu Makan - A Azis; H Abbas; Y Heryandi; E Kusnadi (Media Peternakan, 2011)
The present study was designed to investigate the effect of feeding time restriction on compensatory growth and production efficiency of broiler chickens. Four hundred of 7 days-old unsexed broiler chicken of Lohmann commercial strain were used in the experiment. The treatments were: bird fed ad libitum as a control treatment (R-0); bird had free access to feed during two periods of 2 hours (08:00-10:00 and 16:00-18:00) from 7-14 days of age (R-1) and 7-21 days of age (R-2); bird had free access to feed during two periods of 4 hours (08:00-12:00 and 16:00-20:00) from 7-14 days of age (R-3) and 7-21 days of age (R-4). The treatments were arranged in a completely randomized design with 4 replications. Feed intake and body weight gain of chicken exposed to feeding time restriction on R-1, R-2, R-3 and R-4 were lower (P < 0.01) than those of chicken fed ad libitum. There were no significant different on feed intake and body weight gain during realimentation period. Compensatory growth occured on R-2 and R-4 during the 28 to 42 days of age and similar body weight  with control at age 42 days. Feed conversion ratio on R-2 and R-4 were lower (P < 0.01) feeding time restriction (7-21 days) and realimentation period (28-35 days). It was concluded that feeding time restriction for 8 hours per day from 7 to 21 days of age indicated compensatory growth and similar body weight and had better feed cost and production index than that of control.